2018
DOI: 10.1007/s10694-018-0704-4
|View full text |Cite
|
Sign up to set email alerts
|

Probabilistic Study of the Resistance of a Simply-Supported Reinforced Concrete Slab According to Eurocode Parametric Fire

Abstract: We present the application of a simple probabilistic methodology to determine the reliability of a structural element exposed to fire when designed following Eurocode 1-1-2 (EC1). Eurocodes are being used extensively within the European Union in the design of many buildings and structures. Here, the methodology is applied to a simply-supported, reinforced concrete slab 180 mm thick, with a standard load bearing fire resistance of 90 min. The slab is subjected to a fire in an office compartment of 420 m 2 floor… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
20
0

Year Published

2018
2018
2022
2022

Publication Types

Select...
6
1

Relationship

3
4

Authors

Journals

citations
Cited by 23 publications
(20 citation statements)
references
References 13 publications
(15 reference statements)
0
20
0
Order By: Relevance
“…The thermal conductivity of steel is higher than concrete; therefore, the steel rebar temperature is assumed to be the same as adjacent concrete. It has been shown that 1D heat transfer with constant effective properties results in conservative in‐depth concrete temperature . The lumped mass heat transfer method is used for thermal analysis of the protected beam (Eq.…”
Section: Comparison For a Generic Structurementioning
confidence: 99%
See 1 more Smart Citation
“…The thermal conductivity of steel is higher than concrete; therefore, the steel rebar temperature is assumed to be the same as adjacent concrete. It has been shown that 1D heat transfer with constant effective properties results in conservative in‐depth concrete temperature . The lumped mass heat transfer method is used for thermal analysis of the protected beam (Eq.…”
Section: Comparison For a Generic Structurementioning
confidence: 99%
“…It has been shown that 1D heat transfer with constant effective properties results in conservative in-depth concrete temperature. 25 The lumped mass heat transfer method 21,22 is used for thermal analysis of the protected beam (Eq. 33) and unprotected steel beam (Eq.…”
Section: Comparison For a Generic Structurementioning
confidence: 99%
“…Several fire developments (fully-developed fire) were examined in order to select a critical fire design scenario corresponding to a characteristic fuel load of 1140 MJ/m² and 15% glazing breakage (Heidari et al, 2015). Using OZone model the temperature-time curve of this critical fire design scenario has been obtained and is presented in Fig.…”
Section: Thermal Response Of the Structurementioning
confidence: 99%
“…For example, Shrivastava et al [3] applied performance based earthquake engineering (PBEE) framework for probabilistic studies in structural fire engineering (SFE), where annual rates of exceedance of hazard intensity and structural response were estimated. At the same time, Heidari et al [4] estimated the failure probability of a fire exposed concrete slab to assess its reliability adopting a Monte-Carlo (MC) method, and Gernay et al [5] developed fragility curves to assess the performance of steel building under fire hazard. Out of the available probabilistic approaches, the development of fragility curves has been found to be popular among researchers as it is conceptually easy to understand and allows faster design iterations [5].…”
Section: Introductionmentioning
confidence: 99%